2020
DOI: 10.1093/jas/skaa189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of feeding behavior traits in steers with divergent residual feed intake consuming a high-concentrate diet

Abstract: The objective of this study was to examine the differences in feeding behavior patterns of steers with divergent phenotypes for residual feed intake (RFI). Three trials were conducted with 508 Angus-based composite crossbred steers (body weight [BW] = 309 ± 57 kg) fed a high-concentrate diet in pens equipped with electronic feed bunks (GrowSafe System). Initial and final carcass ultrasound measurements (intra-muscular fat, backfat depth, and rib-eye area) were collected on days 0 and 70, and BW measured at 14-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Time spent at the feeder (TOTFEEDTIME) was comparable with other studies ( Nkrumah et al, 2007 , Haskell et al, 2019 , Parsons et al, 2020 ), where beef steers were fed high concentrate diets through electronic feeders. The TOTFEEDTIME was also comparable with steers fed a mixed diet ( Haskell et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Time spent at the feeder (TOTFEEDTIME) was comparable with other studies ( Nkrumah et al, 2007 , Haskell et al, 2019 , Parsons et al, 2020 ), where beef steers were fed high concentrate diets through electronic feeders. The TOTFEEDTIME was also comparable with steers fed a mixed diet ( Haskell et al, 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…Although lower than results reported in this study, Nkrumah et al (2007) reported positive correlations ( r = 0.27; P < 0.001) between daily feeding time and DMI in steers fed a high concentrate diet. Similarly, positive correlations ( r = 0.13; P < 0.05) between time at the feeder and DMI have been reported in beef steers fed a high corn ( Montanholi et al, 2010 ) and high concentrate ( r = 0.42; P < 0.05; Parsons et al, 2020 ) diets, although a negative correlation ( r = −0.16; P < 0.05) with number of visits to the feeder was also noted ( Montanholi et al, 2010 ). Higher correlations between feeding time and FWI ( r = 0.53–0.95) have been noted in dairy cows fed a total mixed ration ( De Mol et al, 2016 , Pahl et al, 2016 ).…”
Section: Discussionmentioning
confidence: 64%
“…There was no evidence of difference for dimensions or dimension change over the FE period between efficiency groups. This is a common result in RFI studies in growing beef cattle ( Nkrumah et al, 2004 ; Hafla et al, 2013 ; Parsons et al, 2020 ), and in Limousin × Holstein heifers ( Kelly et al, 2010 ). Since animal dimensions are likely highly correlated with animal BW, the dimensions are likely partially captured in the DMI regression used to calculate RFI.…”
Section: Discussionmentioning
confidence: 87%
“…The physiological basis for differences in beef cattle feed efficiency, as defined by residual feed intake (RFI), has been explored extensively. Divergent RFI may be partially explained by differences in nutrient digestibility and rumen volatile fatty acid production (Johnson et al, 2019), feeding behavior (Parsons et al, 2020), and intestinal microbiome composition (Welch et al, 2020). With increasing concerns regarding climate change and narrow profit margins, a recent paper examined efficiency parameters in feed-restricted beef steers (Andreini et al, 2020).…”
Section: Effects Of Feeding Level On Efficiency Of High and Low Resid...mentioning
confidence: 99%